2015
DOI: 10.5114/pm.2015.56312
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian function and ovarian blood supply following premenopausal abdominal hysterectomy

Abstract: IntroductionThe issue of conserving the ovaries at hysterectomy in premenopausal women with benign gynecologic disease has been the subject of considerable controversy. Some clinicians prefer prophylactic oophorectomy in premenopausal women during hysterectomy to prevent future development of malignant changes in conserved ovaries. Other clinicians prefer to conserve apparently normal ovaries, because bilateral oophorectomy in premenopausal women results in an abrupt imbalance, sudden onset of menopausal sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It is controversial whether hysterectomy with ovarian preservation affects ovarian reserve [ 3 ]. The assessment of the ovarian reserve using serial AMH level measurement is considered a useful tool for evaluating the ovarian function after hysterectomy [ 3 11 ], and several studies have been conducted to ascertain whether the postoperative AMH level decreases when compared with the preoperative level, but the results are conflicting [ 11 12 13 14 15 16 17 ]. Some authors reported that hysterectomy with ovarian conservation could accelerate ovarian failure [ 8 9 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is controversial whether hysterectomy with ovarian preservation affects ovarian reserve [ 3 ]. The assessment of the ovarian reserve using serial AMH level measurement is considered a useful tool for evaluating the ovarian function after hysterectomy [ 3 11 ], and several studies have been conducted to ascertain whether the postoperative AMH level decreases when compared with the preoperative level, but the results are conflicting [ 11 12 13 14 15 16 17 ]. Some authors reported that hysterectomy with ovarian conservation could accelerate ovarian failure [ 8 9 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study of 83 patients with symptomatic uterine fibroids who underwent LH with conservation of both ovaries reported that serum AMH levels were decreased significantly at 4 months after LH [ 15 ], On the contrary, Abdelazim et al [ 16 ] reported that the preoperative AMH level (1.75 ± 4.61 ng/mL) of the 220 studied women was not significantly different compared with the AMH level 6 and 12 months after AH (1.78 ± 2.45 ng/mL and 1.81 ± 2.19 ng/mL, respectively). The results from these two studies are in agreement with our results that serum AMH levels significantly decreased immediately after surgery in the LAVH group, but not in the AH group.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data suggest that there is no significant difference in ovarian function after premenopausal hysterectomy up to 1 year. Abdelzeim and colleagues studied ovarian blood supply by Doppler and concluded that the ovarian pulsatile index (PI) reduced and ovarian volume increased indicating increased blood supply and documented maintained AMH, FSH and estradiol levels at 1-year follow-up period [5]. Nahás et al also observed reduced PI values on Doppler ultrasonography suggesting decrease in the resistance flow in the ovarian arteries in women of reproductive age who underwent total abdominal hysterectomy [6].…”
Section: Hysterectomy and Ovarian Functionmentioning
confidence: 99%
“…Toxins, viral infection, cigarette smoking, chemicals and pesticides can speed the ovarian follicle depletion through stimulation of the autoimmune destruction of the ovarian follicles [12,13]. The POI may develop after a hysterectomy in spite of ovarian preservation due to disturbed ovarian blood supply after the hysterectomy [14].…”
Section: Causes Of Primary Ovarian Insufficiencymentioning
confidence: 99%